PENGARUH DUKUNGAN REKAN KERJA, KEPUASAN KERJA, DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN CV. MUDA JAYA UTAMA SIDOARJO - Saputra, Ardi; Kurniawan, Ignatius Soni (Jurnal Manajemen Terapan dan Keuangan, 2024)
Companies can improve company performance by improving human resource performance. Understanding the factor that influence employee performance is important in a company. This research aims to prove the antecedents of employee performance on the variables of coworker support, job satisfaction, and career development. Data were collected through direct survey to employees of CV Muda Jaya Utama in Sidoarjo, East Java. The data were processed through multiple linear regression analysis. This result stated that coworkers and career development have a positive effect on employee performance, but job satisfaction has no effect on employee performance. Strengthening supportive relationships among workers and building a career ladder are implications for leaders to improve employee performance.